Integrated Marketing Communication:Where does it stand in the Malaysian Institutions of Higher Education? - Chu Abdullah, Siti Aishah (National Higher Education Research Institute, Universiti Sains Malaysia, 2016)
Globalization foresees the rapid development of information technology (IT) and the Internet,where by customer’s choices grow at a very fast rate.These factors are well reflected in the extremely competitive market environment in institutions of higher education (IHEs) (Dawes & Brown, 2002).